Patrimônio cultural imaterial, conhecimentos tradicionais e direitos intelectuais coletivos sob a perspectiva socioambiental - Lima, Liliane Mahalem de (2012)
This dissertation addresses the issue of the intangible cultural heritage in the prism of Law. It analyses, thru a socioenvironmental perspective, the legal protection over the knowledges and the collective intellectual rights of traditional populations. As a interdisciplinary, it links diverse legal areas (Constitutional, International, Environmental, Diffuse and Collective) and attempts to take into account some anthropological dimensions. The study begins with a brief history of the consolidation of intangible cultural heritage in Brazil, collated with the simultaneous treatment within the UNESCO. Thereafter, the intangible cultural heritage is conceptualized taking the Federal Constitution of 1988 as is central axis, from which the protective legal instruments -the National Registry and Inventory of Cultural References, developed within the Institute of Artistic Heritage and (IPHAN) are analysed. Then, the text unfolds and deepens the "cultural heritage" taking into account its relations with legal notions of environmental and diffuse heritage and its public concern. Then, it analyses the core concerns of socioenviromentalism in Brazil, taking into account its mais duality: the protection of bio and social diversity. In sequence, the work addresses the formal concept of traditional peoples , and in its wake, the Provisional Measure No. 2.186-16/2001 which, under the Brazilian law, confers protection over the traditional knowledges associated with biodiversity. At the end, this work considers the general proposal to build a sui generis legal system to protect the traditional knowledges and the genetic resources found in the lands occupied by traditional and indigenous populations, as well as other collective rights related to social and biodiversity